Global governance in the pandemic and new paradigms for the post-pandemic period - Araujo Aguirre, Will Erick (2022)
The pandemic affected all countries in different ways, while some had strengthened their governance to face the crisis situation, others had difficulties with the rapid response and efficient fight against the spread of covid-19. In this context, the present work aimed to answer two questions based on these events. The first, related to the development of governance in the pandemic; and, second, the governance paradigms for the post-pandemic era. Interesting answers were found regarding governance, such as its link with other concepts such as collaboration and trust, which represent new models to face the current and future crises. Finally, it is concluded that it is necessary for world governments to analyze the mistakes they made in dealing with the pandemic; as well as, having a more collaborative approach with a more external than internal look towards a more strengthened global governance.